Enhancing tumor cell response to chemotherapy through nanoparticle-mediated codelivery of siRNA and cisplatin prodrug - Xu, Xiaoyang; Xie, Kun; Zhang, Xue-Qing; Pridgen, Eric M.; Ga Young Park; Cui, Danica S.; Shi, Jinjun; Wu, Jun; Kantoff, Philip W.; Lippard, Stephen J.; Langer, Robert; Walker, Graham C.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2013)
Cisplatin and other DNA-damaging chemotherapeutics are widely used to treat a broad spectrum of malignancies. However, their application is limited by both intrinsic and acquired chemoresistance. Most mutations that result from DNA damage are the consequence of error-prone translesion DNA synthesis, which could be responsible for the acquired resistance against DNA-damaging agents. Recent studies have shown that the suppression of crucial gene products (e.g., REV1 , REV3L) involved in the error-prone translesion DNA synthesis pathway can sensitize intrinsically resistant tumors to chemotherapy and reduce the frequency of acquired drug resistance of relapsed tumors. In this context, combining conventional DNA-damaging chemotherapy with siRNA-based therapeutics represents a promising strategy for treating patients with malignancies. To this end, we developed a versatile nanoparticle (NP) platform to deliver a cisplatin prodrug and REV1 / REV3L -specific siRNAs simultaneously to the same tumor cells. NPs are formulated through self-assembly of a biodegradable poly(lactide- co glycolide)- b -poly(ethylene glycol) diblock copolymer and a self-synthesized cationic lipid. We demonstrated the potency of the siRNA-containing NPs to knock down target genes efficiently both in vitro and in vivo. The therapeutic efficacy of NPs containing both cisplatin prodrug and REV1 / REV3L -specific siRNAs was further investigated in vitro and in vivo. Quantitative real-time PCR results showed that the NPs exhibited a significant and sustained suppression of both genes in tumors for up to 3 d after a single dose. Administering these NPs revealed a synergistic effect on tumor inhibition in a human Lymph Node Carcinoma of the Prostate xenograft mouse model that was strikingly more effective than platinum monotherapy.